2016
DOI: 10.3390/su8070632
|View full text |Cite
|
Sign up to set email alerts
|

Peer Effects and Voluntary Green Building Certification

Abstract: Abstract:Empirical evidence is provided to show that peer effects have statistically significant and positive impacts on the diffusion of green building certificates. Application and approval records of green certificates by commercial buildings in NY and AZ are used. The challenge of self-selection is addressed by the usage of fixed effects and the challenge of reflection is addressed by the time lag delay between a building's application and its approval. Empirical results show that an additional approved LE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Another barrier to WTP is that public knowledge of green buildings and certification programs tends to be vague and abstract, whereas reliable information about and tangible experience of green buildings are effective at changing perceptions and increasing WTP [54]. This is consistent with spatial correlations in green building diffusion [105,106] and the observation that homebuyers are generally unequipped to calculate trade-offs between future cost savings and increased borrowing [108]. An increasing prevalence of residential CSB and consequent awareness of benefits could increase homebuyer demand as well as support for subsidies and other policies for residential CSB (Figure 3) but this poses a chicken-and-egg problem.…”
Section: Subsidies and Wtpsupporting
confidence: 60%
See 1 more Smart Citation
“…Another barrier to WTP is that public knowledge of green buildings and certification programs tends to be vague and abstract, whereas reliable information about and tangible experience of green buildings are effective at changing perceptions and increasing WTP [54]. This is consistent with spatial correlations in green building diffusion [105,106] and the observation that homebuyers are generally unequipped to calculate trade-offs between future cost savings and increased borrowing [108]. An increasing prevalence of residential CSB and consequent awareness of benefits could increase homebuyer demand as well as support for subsidies and other policies for residential CSB (Figure 3) but this poses a chicken-and-egg problem.…”
Section: Subsidies and Wtpsupporting
confidence: 60%
“…Indeed, Yau found that household income was correlated with both environmental attitudes and willingness to pay for green homes [53]. Spatial correlations in green building diffusion [105,106] indicate that exposure to and awareness of green buildings and their benefits may also be an important driver, potentially increasing WTP and support for subsidies. In contrast, thermal comfort-if it is considered at all-is just one of many competing considerations in home purchases.…”
Section: Subsidies and Wtpmentioning
confidence: 99%
“…The adoption of green certificates has been rapid, at least in the U.S. There are several studies examining the diffusion of green certificates and determinants of green building adoption (e.g., [39,[128][129][130][131], but they were not covered in this review. For instance, Holtermans and Kok [39] observed that by 2014, almost 40% of the assets in the 30 largest U.S. office markets (measured by square feet) had been either LEED or ENERGY STAR certified.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the green building literature, many researchers, examining the economic value of green building certifications, use this approach (e.g. Qiu et al , 2016, 2014; Fuerst et al , 2012). See Leskinen et al (2020) for a comprehensive review in this field.…”
Section: Methodsmentioning
confidence: 99%